New Aliphatic Alcohol from Ailanthus excelsa Roxb Bark - Kr. Sharma, Surendra; Kumar, Naresh; Singh, Sumitra; Ali, M. (Asian Journal of Chemistry, 2010)
A rare fatty acids, phytosterol and new aliphatic alcohol were isolated from the ethanolic extracts of the stem bark of Ailanthus excelsa Roxb. The structures of these compounds were established on the basis of the chemical reaction and spectral analysis as n-octanyl decasanoate, n-eintriacontane, stigmast-5,22-dien-3β-ol, n-tetratriacontanoic acid and n-eintriacontan-8β-ol.